Investigation of Socio-Economic Characteristics of Wheat Producers on Certified Seed Use: The Case of Ankara Province - Celal CEVHER; Bülent ALTUNKAYNAK (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The aim of this study is to determine the socio-economic factors affecting the use of certified seeds. By determining these factors, it is aimed to increase the income level and thus the welfare of farmers. In addition, by increasing the use of certified seeds, it is desired to obtain quality wheat production and contribute to the development of the grain industry. In the study, producers' opinions on certified seed use were examined in terms of socio-economic variables. As a research area, Ankara province, where certified seed use is common (approximately 20%), was chosen. Land size was taken into account in determining the sampling volume. The primary data of the study were collected by questionnaire method from 318 manufacturers. Secondary data was obtained from agricultural organizations. According to the results of the research, the rate of adoption of certified wheat seed was determined as 58.7%. 90.6% of the producers stated that the seed support given was not sufficient and 88.7% of the seed prices were high. The rate of producers stating that there are suitable alternative seed varieties in the research area is 83.6%. It has been determined that the training level of the producers has a significant impact (p <0.05) on the adequacy of the supports and their opinions on seed prices. The producer's residence and income levels have had a significant (p <0.05) effect on alternative seed selection. As a result, it has been concluded that certified seed support provided by the Ministry of Agriculture and Forestry affects quality seed use, increase in gross production value and decrease in production costs.